2008
DOI: 10.4062/biomolther.2008.16.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Ginsenoside Rb1,Rg3, and Panax ginseng Head Butanol Fraction on Inflammatory Mediators from LPS-Stimulated RAW 264.7 Cells

Abstract: − Panax ginseng C.A. Mayer (Araliaceae, P. ginseng) has been used for the enhancement of vascular and immune functions in Korea and Japan for a long time. Ginsenoside Rb 1 and Rg 3 isolated from P. ginseng head-part butanolic extract (PGHB) were investigated for anti-inflammatory activity. Ginsenosides and PGHB did not affect the cell viability within 0 -100 µg/ml concentration to RAW 264.7 murine macrophage cells. Ginsenosides and PGHB inhibited partly lipopolysaccharide (LPS)-induced nitrite production in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Typhimurium up to 500 μM concentrations. In addition, Lee and Jeong [ 35 ] and Yang et al [ 36 ] reported that Rg3 did not affect the viability of RAW 264.7 cells at a maximum tested concentration of 100 μg/mL. In the present study; however, 100 μM of Rg3 reduced the viability of Caco-2 and RAW 264.7 cells.…”
Section: Discussioncontrasting
confidence: 62%
“…Typhimurium up to 500 μM concentrations. In addition, Lee and Jeong [ 35 ] and Yang et al [ 36 ] reported that Rg3 did not affect the viability of RAW 264.7 cells at a maximum tested concentration of 100 μg/mL. In the present study; however, 100 μM of Rg3 reduced the viability of Caco-2 and RAW 264.7 cells.…”
Section: Discussioncontrasting
confidence: 62%
“…8 In addition, Rd was found to exert radioprotective effects on rat intestinal epithelial cells following high‐dose irradiation 9. Rg 1 and Rb are also known to possess strong immune system‐stimulating properties 10, 11. Therefore, it would be valuable to develop a method to efficiently extract these ginsenosides from low‐quality ginseng.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that ginseng and its constituent ginsenosides can modulate indices of stress, fatigue, and learning [7][8][9]. In humans, ginseng improves performance on a memory task [10], suppresses granulocytopoiesis [11], and regulates the erythropoiesis after paradoxical sleep deprivation [12].…”
Section: Introductionmentioning
confidence: 99%